Synthesis, Characterization and Evaluation of Starch Acetate as Microencapsulating Agent for Controlled Release of Glipizide - Chowdary1, K.P.R.; Radha2, G.V. (Asian Journal of Chemistry, 2011)
Starch acetate with a degree of substitution about 1.5 could be synthesized by acetylation of potato starch with acetic anhydride. Starch acetate microcapsules of glipizide were prepared by an industrially feasible emulsification-solvent evaporation method and the microcapsules were studied with a view to evaluate starch acetate as microencapsulating agent. The starch acetate microcapsules prepared are spherical, discrete, free flowing and multinucleate, monolithic type. Microencapsulation efficiency was in the range 94-98 %. Glipizide release from the microcapsules was slow over 24 h and depended on core: coat ratio, wall thickness and size of the microcapsules. Drug release was by Fickian diffusion mechanism. Good linear relationships were observed between wall thickness of the microcapsules and release rate. Starch acetate was found suitable as microencapsulating agent and the starch acetate microcapsules exhibited good controlled release characteristics.